PERAN MA’HAD AL-ZAYTUN DALAM PENGELOLAAN LINGKUNGAN HIDUP PERSPEKTIF UNDANG-UNDANG NOMOR 32 TAHUN 2009 DAN FIQH SIYASAH - Baldan Al-Kautsar, Muhammad; Ngainnur Rohmah, Siti; Taufiqurrahman (Causa: Jurnal Hukum dan Kewarganegaraan, 2024)
Ma'had Al-Zaytun plays an active role in environmental management by applying sustainability principles, such as conservation and efficient utilization of natural resources. The institution manages land for agriculture, livestock, and forestry in an environmentally friendly way, as well as including environmental education in its curriculum to raise santri's awareness of the importance of nature conservation. This research aims to analyze the role of Ma'had Al-Zaytun in environmental management, both from the perspective of Law Number 32 of 2009 concerning Environmental Protection and Management and the perspective of Fiqh Siyasah. The author uses a normative juridical approach by analyzing primary data sources, namely Law 32/2009 and the book Fiqh Siyasah by Prof. H.A. Djazuli, as well as secondary sources such as related books and articles.The results show that Ma'had Al-Zaytun implements the principles of Law 32/2009 by turning arid land into productive green areas, through tree planting and efficient water management technology. From the perspective of Fiqh Siyasah, Ma'had Al-Zaytun applies the principle of “Amana” (moral responsibility) in natural resource management and the principle of “Maslahah” (public interest) to ensure environmental policies provide equitable benefits for the institution and the surrounding community. By integrating environmental education into its curriculum, Ma'had Al-Zaytun not only maintains ecological balance, but also teaches the importance of environmental conservation in accordance with Islamic teachings. Kata kunci: Ma'had Al-Zaytun, Environmental Management, Fiqh Siyasah